Analisis Strategi Inovasi Produk Ramah Lingkungan pada UMKM Sebagai Upaya Penciptaan Nilai Berkelanjutan dalam Perspektif SDGs - Putri, Deya Aulia; Agustina, Nina; Widiyanti, Amelia; Zikri, Muhamad; Sanjaya, Tiara Putri; Mufliha, Widi Aulia; Nurmala, Siti; Monita, Bunga Fleta Falihah (Sharia Journal and Education Center Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting the achievement of the Sustainable Development Goals (SDGs), yet they still face environmental challenges arising from their production activities. This study aims to analyze environmentally friendly product innovation strategies in MSMEs as an effort to create sustainable value from the SDGs perspective through a literature review approach. The findings indicate that the adoption of eco-friendly product innovation, including the use of sustainable materials, efficient production processes, and strengthened green branding, enhances MSME competitiveness while simultaneously generating economic, social, and environmental value. This strategy significantly contributes to the achievement of SDGs, particularly in inclusive economic growth, responsible consumption and production, and environmental protection.